Development of Smart Parking Security Application Using LoRa GPS Based IoT Geo-fencing - Azhar, Azad Affandi Ghadaffi; Jong, Siat Ling (Evolution in Electrical and Electronic Engineering, 2025)
This paper presents the development of a smart parking security application using a LoRa GPS-based IoT geo-fencing system. The system improves vehicle monitoring and security by integrating real-time location tracking with instant alert notifications. An ESP32 microcontroller, equipped with a Neo-6M GPS module and SX1278 LoRa transceiver, transmits vehicle coordinates to a Firebase Realtime Database. A Flutter-based mobile application retrieves this data, visualizes the vehicle’s position on Google Maps, and triggers notifications when the vehicle exits predefined geo-fencing zones. The system was tested at two different geographic boundaries and successfully detected unauthorized vehicle movements with immediate alerts. Experimental results demonstrate the effectiveness of LoRa communication for long-distance monitoring and the practical application of IoT in enhancing parking security. The system achieved an average detection accuracy of 97.5%, highlighting its strong real-time responsiveness and boundary detection precision.